IMPLEMENTATION OF THE CITY WITHOUT SLUMS (KOTAKU) PROGRAM IN TANJUNG BALAI KARIMUN, KARIMUN REGENCY IN 2017 - Oky Efrieldy Putra Hang Jebat; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The problem of slum settlements is still the main problem faced by urban settlements in Indonesia to date, the rate of population growth through the urbanization process and the rate of population growth arising from the high annual birth rate and the availability of supporting facilities and infrastructure for residential areas have not been met properly and below the Standard Minimum Service (SPM) such as lack of provision of public service facilities and infrastructure, low quality of drinking water, drainage, solid waste, solid waste services and building density that can have an impact on fulfilling fire protection. One of the areas in Karimun Regency which is included in the slum area is Tanjung Balai Karimun. Tanjung Balai Karimun has a slum area of 49.76 Ha, of which there are 4 sub-districts with different slum areas, the Telaga Tujuh and Kuda Laut areas in Sungai Lakam Barat and Baran Barat Villages 25.79 Ha, Pulau Kambing and Kampung Orari, Kelurahan Sungai Lakam Barat and Sungai Lakam Timur is 17.20 Ha, Gang Asoka Area, Kelurahan Baran Timur 4.67 Ha, and Baran Barat Area Kelurahan Baran Barat 2.10 Ha. This study aims to determine the implementation of the City Without Slums Program (KOTAKU) in Tanjung Balai Karimun, Karimun Regency in 2017 and to analyze the factors that influence the implementation of the KOTAKU Program, namely problem characteristics, policy characteristics, and policy environment. The research locations are the Department of Housing, Settlement Areas and Cleanliness of Karimun Regency, KOTAKU Program Coordinator of Karimun Regency, and Tanjung Balai Karimun of Karimun Regency which is the main source of this research. The result of this research is that the implementation of the KOTAKU Program in Tanjung Balai Karimun, Karimun Regency in 2017 has not been optimal. This is because the implementation of the KOTAKU program in Tanjung Balai Karimun, Karimun Regency in 2017 has not met the characteristics that affect the successful implementation of a program.Keywords: KOTAKU, Problem Characteristics, Policy Characteristics, Policy Environment.